Education and training for industrial biotechnology and engineering biology. Issue 1 (11th June 2018) - Delebecque, Camille J.; Philp, Jim
Abstract : Industrial biotechnology is focused on the production of bio‐based fuels, chemicals and materials such as plastics and textiles. Engineering biology, synonymous with synthetic biology, provides a platform technology that brings an engineering approach to harnessing biotechnology for industrial production. The two combine within the political construct of the future bioeconomy, in which bio‐based gradually replaces fossil‐based production. There are many barriers to this future, including technical, political and social aspects. Behind all of these is a need for a new form of workforce not seen before, in which various skills and knowledge bases merge and combine. The required multi‐ and interdisciplinary skills challenge higher education to get out of the discipline‐dominated paradigm. This study examines some of the current and future critical issues and provides some examples of how higher education is rising to the challenge.